Digitalization in Indian agriculture: Reorienting Indian farming towards smart agriculture - Burman, R Roy; Mahra, Girijesh Singh; Saini, Sushmita; Jha, S K; Gautam, U S (Indian Farming, 2023)
Information and Communication Technologies (ICTs) has proved to be extremely beneficial for farmers and helped them in getting easy access to customized digital information regarding improved varieties, cropping pattern, use of high-yielding seeds, fertilizer application, pest management, marketing, entrepreneurship etc. The most effective and widely used instrument for agricultureextension to share information and provide advice to farmers is the mobile phone. There are several important mobile apps developed by the Ministry of Agriculture and Farmers Welfare, Government of India and other organisations which are using Geographic Information System (GIS) and Data Analytics of Smart Agriculture to deliver accurate information to the farmers at their doorstep. IoTand AI offers wide range of applications in agriculture.